Green House Project: Perception in Wilayah Persekutuan - Yaser Abdulwahab A A,; Sulzakimin M,; Roshartini, O,; Md Asrul Nasid1,; Ta Wee S,; Mohammad Syabilee N L,; Adaji A A, (Journal of Technology Management and Business, 2019)
Abstract: Green house is becoming a strong momentum in the construction industry after recognizing many negative environmental issues & and problems and potential social and economic benefits around the world. However, developers still using conventional way to construct the housing. This gives huge impact to our environment and also human health. Meanwhile, there are actually some barriers hindering developers to adopt this in their projects. In this study, the perception of stakeholders on green housing will be reviewed. This study shows alertness on environment and increase the green house project among developers. This study examines the perceptions of the developers in Wilayah Persekutuan on green housing sector for the next 20 years. The outline of Green house rating system, improvement of alertness and knowledge among the stakeholders, support from the government and local industry. Therefore, the current situation in rules and regulation, lack of public interest and demand, lack of interest of organization, local government enforcement and project cost escalation would delay a faster progress.  Keywords: Construction, green house, sustainable